APPROACHING ARABIC LEARNING THROUGH THE USE OF THE GOOGLE WEBSITE - Moch Wahib Dariyadi (Prosiding Konferensi Nasional Bahasa Arab, 2021)
Teachers must maximize their use of ICT-based learning media in the face of the covid-19 pandemic. As a result, various efforts are required in the learning process, including the use of ICT-based learning media to assist teachers. The critical nature of developing teachers' competence and skills in utilizing and optimizing ICT-based learning media necessitates the need for teacher training in creating and using ICT-based learning media. From September 11 to September 17, 2021, training on the creation and use of Google sites as learning media will be held. This training aims to increase Arabic language teachers' competence through the use of Google Sites as a learning medium. This training will be conducted in two stages, the first of which will involve the delivery of material on the creation and use of Google sites as learning media, and the second of which will involve direct practice in the creation and use of Google sites as learning media. Lectures, questions and answers, and experiments are used in this training. The enthusiasm of the participants fueled this training, which drew 1645 Arabic MGMP teachers from across Indonesia. This training enhances participants' knowledge and abilities, as well as their ability to create and use Google sites as instructional media. The results of the questionnaire distributed to teachers following this activity indicated that it was extremely beneficial and that they hoped similar activities would be held again the following year.